Nanoparticle-assisted stabilization of metal species as an alternative to conventional approaches for avoiding volatilization errors in total reflection X-ray fluorescence: A review - de la Calle, Inmaculada; Romero, Vanesa; Lavilla, Isela; Bendicho, Carlos (Spectrochimica acta. Part B: Atomic spectroscopy, 2020)
Total Reflection X-Ray Fluorescence spectrometry (TXRF) provides many advantages for metal and metalloid analysis. In general, the sample should be prepared as a thin film. To that end, for the analysis of liquid, suspensions or solids previously digested, a small aliquot of the sample is dropped on the sample carrier (e.g. quartz reflector). However, main inconveniences of this technique are the low sensitivity achieved for certain elements depending on their fluorescence yield (also related with the atomic number and the line series selected for the element quantification), and the high volatility of certain elements and compounds (such as oxides, fluorides, chlorides and hydrides) due to their loss during sample drop evaporation performed in the quartz reflector as a consequence of sample preparation before TXRF analysis. Published papers on this subject are mainly related to mercury, but volatilization losses of selenium, arsenic, lead and cadmium and halogens have also been reported. Different analytical approaches have been developed to improve the sample preparation step so as to avoid losses of volatile elements and compounds before TXRF analysis, which are summarized in this review. These strategies include slurry sampling, amalgamation, complexation, adsorption onto membranes, immobilization on quartz reflectors and more recently approaches using nanomaterials like metallic nanoparticles, carbon dots and graphene that can also preconcentrate target analytes. Potentials and pitfalls of these strategies are discussed in this review, as well as other tentative approaches. [Display omitted] •Sample pretreatment to avoid element losses by TXRF is reviewed.•Elements prone to be lost by volatilization (especially Hg) are targeted.•Analytical strategies with and without NPs are discussed.•Amalgamation, membrane adsorption, immobilization and complexation are suitable strategies.•Graphene, graphene oxide, carbon nanotubes, Ag and Pd NPs can be used for sorption.